2005
DOI: 10.1111/j.0022-1112.2005.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex and shoal size on shoaling behaviour inDanio rerio

Abstract: Male and female zebra fish Danio rerio were given choices of shoals that differed in sex and size. Male zebra fish preferred to associate with female shoals over male shoals, but had no preference when given a choice between a mixed-sex shoal and either a male or female shoal. Female zebra fish showed no significant preference when given a choice between male and females shoals, nor between mixed-sex shoals and either male or female shoals. When given choices between shoals of differing size, females preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 32 publications
5
93
1
Order By: Relevance
“…The size and composition of the stimulus shoal are also important, and several features of shoal mates have been shown to also induce preferential responses in zebrafish, including sex and number of shoal members shown, sex ratio within the stimulus shoal, body size, stripe pattern, and pigmentation of stimulus fish (Kitevsky and Pyron, 2003;Ruhl and McRobert, 2005;Qin et al, 2014;Seguin & Gerlai, 2017;Seguin et al, unpublished results).…”
Section: The Effect Of Environmental Stimuli On Shoalingmentioning
confidence: 99%
“…The size and composition of the stimulus shoal are also important, and several features of shoal mates have been shown to also induce preferential responses in zebrafish, including sex and number of shoal members shown, sex ratio within the stimulus shoal, body size, stripe pattern, and pigmentation of stimulus fish (Kitevsky and Pyron, 2003;Ruhl and McRobert, 2005;Qin et al, 2014;Seguin & Gerlai, 2017;Seguin et al, unpublished results).…”
Section: The Effect Of Environmental Stimuli On Shoalingmentioning
confidence: 99%
“…Spawning occurred in the morning, when the fish dropped to the bottom and darted quickly over the substrate where they mated and deposited eggs (Hutter et al 2010). Although zebrafish are often described as ''broadcast spawners'' (Ruhl and McRobert 2005), such behaviour appears to be a laboratory artefact from studying fish in small, crowded aquaria (Hutter et al 2010). Zebrafish lack conspicuous sexual dimorphisms and the sexes are often not easy to distinguish, at least for humans; however, contrary to what is sometimes suggested (Pritchard et al 2001), they are not monomorphic.…”
Section: Introductionmentioning
confidence: 99%
“…This finding implies that females are more attuned to sex differences than males (at least for body shape); however, another study using actual fish for visual stimuli found the opposite result. When presented with shoals of zebrafish, males were more attracted to female over male shoals (Ruhl and McRobert 2005). However, because size was not controlled (on the contrary, females for the experiment were chosen by their distended abdomens), this result may have been due to males' preference for large females (Hutter et al 2010) rather than sex discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…When discriminating numbers above 4, ratios up to 0.5, e.g. 3 versus 6 or 5 versus 10 are differentiated by angelfish, Pterophyllum scalare (Gómez-Laplaza 2012), guppies (Piffer et al 2013) and zebrafish, Danio rerio (Ruhl and McRobert 2005). Mosquitofish, Gambusia affinis (Agrillo et al 2007), and three-spined sticklebacks, Gasterosteus aculeatus, are also shown to discriminate ratios of 0.66 (e.g.…”
Section: Introductionmentioning
confidence: 99%